2006
DOI: 10.1152/ajprenal.00439.2004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular physiology of renal organic anion transporters

Abstract: Recent advances in molecular biology have identified three organic anion transporter families: the organic anion transporter (OAT) family encoded by SLC22A, the organic anion transporting peptide (OATP) family encoded by SLC21A (SLCO), and the multidrug resistance-associated protein (MRP) family encoded by ABCC. These families play critical roles in the transepithelial transport of organic anions in the kidneys as well as in other tissues such as the liver and brain. Among these families, the OAT family plays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
169
0
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 217 publications
(178 citation statements)
references
References 78 publications
3
169
0
6
Order By: Relevance
“…Substrates for this transporter include many drugs known to be associated with SJS. A partial list includes NSAIDs, β-lactam antibiotics, diuretics, glucuronide conjugates, and cysteine conjugates [54]. OAT1 has a transport role in a number of vital metabolic pathways including the citric acid cycle, pyruvate, nucleotide, polyamine, and fatty acid metabolism [55].…”
Section: Results: Disproportionate Molecular Targets Identified By Damentioning
confidence: 99%
“…Substrates for this transporter include many drugs known to be associated with SJS. A partial list includes NSAIDs, β-lactam antibiotics, diuretics, glucuronide conjugates, and cysteine conjugates [54]. OAT1 has a transport role in a number of vital metabolic pathways including the citric acid cycle, pyruvate, nucleotide, polyamine, and fatty acid metabolism [55].…”
Section: Results: Disproportionate Molecular Targets Identified By Damentioning
confidence: 99%
“…Gene inactivation of other urate transport proteins URAT1, OAT1, and OAT3, which are located in the proximal convoluted tubule (23,24), leads to only moderate dysregulation of urate homeostasis. In marked contrast, we show that Glut9 gene inactivation leads to greatly elevated urate excretion and suppressed renal reabsorption with a fractional excretion of urate of 100% in G9KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…This tissue distribution distinguishes OAT7 from other OATs characterized to date, because most OATs are found mainly in kidney and expressed in multiple tissues. 21,22 Amongst OATs, OAT2 is considered to be important for hepatic organic anion handling because of its abundant expression in the liver. It also is expressed moderately in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…20 We and others identified another major sodium-independent multispecific organic anion transporter (OAT) group in the SLC22 family that mediates the transport of a wide variety of organic anions. 21,22 Expressed in multiple tissues such as the kidney, placenta, liver, and brain, OATs play important roles in the elimination of drugs and their metabolites. We reported that OAT1-4, expressed in the basolateral or apical membrane of renal tubular cells, mediate the transport of various organic anions.…”
mentioning
confidence: 99%